Designing Embedded Case Study Research Approach in Educational Research - Cucuk Budiyanto; Adi Prananto; Felix Ter-Chian Tan (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2019)
Despite the case study research method has been widely adopted in qualitative research, few scholarly articles addressed the comprehensive guidance on the use of embedded case study research design. This paper aims to contribute to the literature by demonstrating the use of embedded case study research design in qualitative research. A pseudo case was exemplified by exploring the relationship between a holding company and its subsidiary companies of a corporate group. What construct a case and the rationale for the case being studied is exemplified. The paper further outlines the research protocol, the procedure of inquiry, and the design of the embedded case analysis. A brief explanation of the context of the case enriches the understanding of the investigated cases.